MicroRNA implications in the etiopathogenesis of ankylosing spondylitis. Issue 8 (7th March 2018) - Mohammadi, Hamed; Hemmatzadeh, Maryam; Babaie, Farhad; Gowhari Shabgah, Arezoo; Azizi, Gholamreza; Hosseini, Fatemeh; Majidi, Jafar; Baradaran, Behzad
Abstract : Ankylosing spondylitis (AS) is a chronic immune‐mediated inflammatory disease that affects both axial and peripheral skeletons as well as soft tissues. Recent investigations offer that disease pathogenesis is ascribed to a complex interplay of genetic, environmental, and immunological factors. Until now, there is no appropriate method for early diagnosis of AS and the successful available therapy for AS patients stay largely undefined. MicroRNAs (miRNAs), endogenous small noncoding RNAs controlling the functions of target mRNAs and cellular processes, are present in human plasma in a stable form and have appeared as possible biomarkers for activity, pathogenesis, and prognosis of the disease. In the present review, we have tried to summarize the recent findings related to miRNAs in AS development and discuss the possible utilization of these molecules as prognostic biomarkers or important therapeutic strategies for AS. Further examinations are needed to determine the unique miRNAs signatures in AS and characterize the mechanisms mediated by miRNAs in the pathology of this disease. Abstract : This review intends to highlight recent investigations associated with miRNAs in AS development and discuss the possible application of miRNAs as prognostic biomarkers or treatment strategies for this disease.